A new hypothesis to explain skin cancer risk in kidney allograft recipients. Issue 1 (February 2021) - Viggiano, Davide; Lee, Michael W; Simeoni, Mariadelina; Capasso, Giovambattista; Capasso, Anna
Kidney transplant (KT) recipients have an increased risk for specific types of cancer. Some forms of incident cancer are similarly present in other diseases where T-cells are depleted, such as HIV-infection: specifically, non-Hodgkin lymphoma and Kaposi's sarcoma. Conversely, other forms of highly incident cancers in KT patients, primarily non-melanoma skin cancer (squamous cell carcinoma and basal cell carcinoma), are specific to this condition. By comparing HIV-related cancers, general cancer incidence, and the association of immunotherapy with cancer incidence, we suggest that the high incidence of non-melanoma skin cancer seen in KT patients is mediated by off-target effects of calcineurin inhibitors in the skin, combined with a "permissive" cancer microinflammatory environment.